Implementation of Post-Pandemic Learning Independence Culture in Elementary Schools - Zulaika, Zulaika; Fitria, Happy; Fitriani, Yessi (Journal of Social Work and Science Education, 2024)
The COVID-19 pandemic has had an impact on the Indonesian education system, causing changes in students’ cultural learning patterns and decreased creativity. Schools are restructuring their learning culture to focus on students and adapt to the environment. Indonesian government education system law no. 20 of 2003 mandates cultural values, cultural acculturation, and fostering independent learning. Teachers play an important role in motivating students and implementing a culture of independent learning, which has a positive impact on their learning process. This research aims to determine the effectiveness of implementing a culture of independence in learning at SD Negeri 1 Pangkalan Baru, Central Bangka Regency, Bangka Islands Province. This research uses a phenomenological approach and qualitative methods to collect data and information from informants. The research aims to build a culture of independence, minimize teacher-student understanding and increase effective communication relationships between students. The research was conducted at SD Negeri 1 Pangkalan Baru Central Bangka, Bangka Belitung Islands Province. Data collection in qualitative research includes observation, interviews, and documentation and data can be taken from several sources. The analysis and sharpness of qualitative research is greatly influenced by the strength of the words and sentences used in the literature. The objects of the research were students at SD Negeri 1 Pangkalan Baru, Central Bangka Regency, Bangka Belitung Islands Province. The results of the research show that at SD Negeri 1 Pangkalan Baru, the focus on independent learning is emphasized through emotional intelligence, cultural habituation, and the character education system. The Pancasila learner profile emphasizes six dimensions: faith, piety, noble character, global diversity, and independence. Independent learning involves creating a study schedule, discussing with teachers, and applying critical reasoning skills. Constructivism theory encourages critical thinking, creativity, and problem solving, thereby leading to increased motivation and academics success.